Alternative Means Testing Options Using CBMS - Celia M. Reyes (Philippine Institute for Development Studies (PIDS), 2006)
The study proposes an alternative means to the present manner of identifying eligible Philhealth beneficiaries through the use of three criteria, namely: income, ownership of assets and socioeconomic characteristics, and electricity consumption. The information/data gathered in evaluating the criteria are sourced with the use of the community-based monitoring system (CBMS) approach. Given that many of the poor households may not have verifiable records/documents regarding the first criterion–income–the study recommends the adoption of a two-stage screening method using the other two criteria. Households are first classified on the basis of socioeconomic variables that are predictors of income-based poverty status. This is followed by a second stage screening based on electricity consumption for those who passed the first screening. The proposed methodology addresses the problem of undercoverage/exclusion of possible eligible beneficiaries from the program that is evident in the present manner of identifying beneficiaries.
Keywords: 330; community-based monitoring system; PhilHealth indigent program; income-based poverty; assets ownership; electricity consumption; targeting of beneficiaries